Aktivitas Antidiabetes Ekstrak Etanol Kulit Batang Faloak (Sterculia quadrifida R.Br.) Terhadap Tikus Wistar yang Diinduksi Aloksan - Diki Dongga, Irene Rambu Yety; Sunarti, Sunarti; Sunarti, Titik (Jurnal Farmasi Indonesia, 2016)
Diabetes mellitus is a chronic disease with hyperglycemic and oxidative stress component that can lead to various complications. The stem bark of faloak have been used traditionally to treat diabetes by local people in East Nusa Tenggara. Therefore, this research aimed to study antidiabetic activities in alloxan-induced rats of faloak ethanolic extract. The all rats were divide at random into group I : normal control; groups II : diabetic control; group III : standart (glibenclamide); group IV â?? VI : administrations group of faloak stem bark ethanol extract at a dose of 65 mg / kg, 130 mg / kg and 260 mg / kg for 14 days. Blood samples were collected from rats in duration 0 â?? 14 days for T0, T4, T7 and T14 after alloxan treatments. The results showed that ethanol extract of faloakâ??s bark dose of 260 mg/ kg on 14 days had decreased blood glucose levels 46,07%, no different glibenclamide group. The dose of 65 mg/kg and 130 mg/kg reduced glucose level respectively 26,32 % and 38,09 %.